Synthesis of new boron containing compound (CCB-2) based on curcumin structure and its cytotoxic effect against cancer cells - Edy Meiyanto&, Ratna Asmah Susidarti&, Riris Istighfari Jenie&, Rohmad Yudi Utomo&, Dhania Novitasari, Febri Wulandari, Mitsunori Kirihata (Journal of Applied Pharmaceutical Science, 2020)
Boron containing compound (BCC) offers the potential further development for therapy against malignant cancers. We successfully synthesized a new compound based on curcumin structure (curcumin analogue) containing boron atoms, namely, CCB-2 and revealed its cytotoxic activities on various cancer cell lines. The compound was simply synthesized based on aldol condensation using acetone and 4-formylphenyl boronic acid resulted a symmetry CCB-2. The compound was then tested for cytotoxic activities in several cell lines. CCB-2 demonstrated cytotoxic effect on MCF-7/HER-2, MCF-7, RAW 264.7, and 4T1 with IC50 value of 12 μM, 54 μM, 26 μM, and < 10 μM, respectively, while less toxic in fibroblast cells. This compound performed superior cytotoxic against highly metastatic cancer cell, 4T1. In addition, CCB-2 induced cells accumulation in G2/M phase, but decreased the accumulation of intracellular Reactive oxygen species level in 4T1 cells. All the data suggest that this new compound is promising to be developed as anti-cancer agent rather than for Boron Neutron Capture Therapy-based cancer therapy.
Keywords: Boron containing compound CCB-2, curcumin analogue, cytotoxicity, cancer cells.